ANTICORROSIVE ZINC COVERINGS ON STEEL ARTICLES: PROSPECTS OF THERMAL DIFFUSION COVERINGS - V. M. Konstantinov; N. I. Ivanitskiy; L. A. Astrejko (Литьë и металлургия, 2013)
The analysis of existing zinc coatings on steel details is carried out. The reached results on development of energyresourcesaving technologies of thermal-diffusion galvanization are reported.